2021
DOI: 10.1111/1751-7915.13765
|View full text |Cite
|
Sign up to set email alerts
|

Activity of bacteria isolated from bats against Pseudogymnoascus destructans in China

Abstract: White-nose syndrome, a disease that is caused by the psychrophilic fungus Pseudogymnoascus destructans, has threatened several North America bat species with extinction. Recent studies have shown that East Asian bats are infected with P. destructans but show greatly reduced infections. While several factors have been found to contribute to these reduced infections, the role of specific microbes in limiting P. destructans growth remains unexplored. We isolated three bacterial strains with the ability to inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…For those pathways with gene relative abundances >0.1%, different bat species enriched similar pathways but most of them had significant variation across hosts ( Figures 3B,C ). We analyzed phenazine biosynthesis because of the presence of anti- P. destructans active substances in this pathway ( Li et al, 2022 ); however, no significant variation in gene abundance was found among the bat species ( Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For those pathways with gene relative abundances >0.1%, different bat species enriched similar pathways but most of them had significant variation across hosts ( Figures 3B,C ). We analyzed phenazine biosynthesis because of the presence of anti- P. destructans active substances in this pathway ( Li et al, 2022 ); however, no significant variation in gene abundance was found among the bat species ( Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…leucogaster in Gezi cave were the highest ( Supplementary Figures 1A,B ), and the OTU richness was also the highest, suggesting the production of more antifungal metabolites (degradation pathways) or more effective competition with the pathogen for resources ( Longo et al, 2015 ). The Pseudomonas isolated from R. ferrumequinum and M. petax in Gezi cave in vitro efficiently inhibited the growth of P. destructans ( Li et al, 2022 ). The BSM class pathways may be involved in bacterial competition within the community and in protecting the host against pathogens ( Rebollar et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The knowledge of the skin microbiota could prove important in counteracting the white-nose syndrome (WNS), a fungal disease caused by Pseudogymnoascus destructans that is responsible for the deaths of millions of bats in North America (see in the Fungi section; Hoyt et al, 2021 ). Several bat’s skin bacteria are able to inhibit the growth of this fungus such as Pseudomonas and Streptomyces genera ( Hoyt et al, 2015 ; Hamm et al, 2017 ; Lemieux-Labonté et al, 2017 ; Li A. et al, 2021 ; Li Z. et al, 2021 ).…”
Section: Bacteriamentioning
confidence: 99%